O-50 Exposome project for health and occupational research (EPHOR) mega cohort. (14th March 2023) - Turner, Michelle C; Johannessen, Ane; Pronk, Anjoeka; Huss, Anke; Garde, Anne Helene; Straumfors, Anne; Ge, Calvin; Svanes, Cecilie; Janson, Christer; Falkstedt, Daniel; Meulengracht Flachs, Esben; Kolstad, Henrik; et al.
Abstract : Introduction: The EPHOR project is constructing a mega cohort for pooled analysis of data from multiple European cohort studies of occupation and health. The objective is to provide new evidence of the impact of occupational exposures on the risk of major non-communicable diseases, through systematic and agnostic analyses across the life-course. Materials and Methods: Cohorts are registered in an online inventory. Cohort data and occupational information are being harmonised and documented in an online variable catalogue, and will be linked with a newly developed European Job-Exposure Matrix (EuroJEM) characterising multiple: chemical and particle, ergonomic, physical, and psychosocial exposures and precariousness. Cohort information on working time will also be harmonised. Knowledge gaps on occupational exposures in relation to major non-communicable diseases were identified. Both meta-analysis and decentralized analysis approaches will be used, as appropriate. Ethics approval is provided by all relevant committees. Results: Currently 29 European cohorts covering a broad range of countries as well as multi-country studies are participating, containing more than 20 million participants. Cohort designs range from smaller scale studies including hundreds to thousands of workers with detailed exposure and/or outcome characterisation, to large-scale general population cohorts including multiple millions of participants with occupational information captured using registry-based methods. Cohorts were largely established and followed-up during the 2000s through the current time, though some were established earlier. Occupational information primarily entails the working lifetime or follow-up period. Outcome information includes disease incidence, disability, and mortality. In some studies, information about genetics, epigenetics, other biomarkers and clinical/functional evaluations is available. Analysis will address knowledge gaps of cancer, respiratory, cardiovascular/metabolic, and neurodegenerative diseases, mental and musculoskeletal disorders, and work participation. Conclusions: We expect the mega cohort will be a useful long-term resource to study relationships of occupations, work-related exposures and health in Europe to inform policy and prevention.